Gerakan dan pendidikan literasi media kritis di indonesia (studi terhadap yayasan pengembangan media anak) - Syukri, Muhammad; Sujoko, Anang; Safitri, Reza (MEDIAKOM : Jurnal Ilmu Komunikasi, 2019)
This paper aims to present about media literacy movements and education carried out by the Children's Media Development Foundation (YPMA) with a perspective on media political economy studies. YPMA was chosen as the object of research because it is widely known as an institution that concentrates and is consistent in the development of child literacy in Indonesia. This paper focuses on the strategy of movement and media literacy education carried out by YPMA during the period 2006 to 2016. The method used is qualitative with descriptive research type. It is known that YPMA has a target in every program implementation is at the age of children and adolescents. Therefore, YPMA devised several strategies such as socialization and campaigns through schools and other educational institutions, held training for teachers, and emphasized the involvement of parents as a significant other in media literacy education.Keyword: Media Literacy, YPMA, Political Economy,